Enzyme Histochemical Assessment of Mitochondrial Functions in Patients with Myopathic form of Limb-Girdle Syndrome. (24th November 2011) - Verma, Ritu; Pal, Lily; Pandey, Rakesh; Paliwal, Vimal Kumar
Abstract : Isolated mitochondrial myopathy is characterized by slowly progressive limb-girdle muscle weakness and resembles other muscle disorders like muscular dystrophy or inflammatory myopathy on clinical grounds. Identification of abnormal mitochondria in the muscle tissue is required for the diagnosis of isolated mitochondrial myopathy. Therefore, this study was done with aim to identify patients with isolated mitochondrial myopathy among those with limb-girdle muscle syndromes of undefined cause. Forty-eight consecutive patients with limb-girdle muscle disease from 2008 to 2010 were screened for Duchenne/Becker muscular dystrophy gene deletion, metabolic myopathy, and drug-induced and endocrine causes. Twenty patients without an identifiable cause were subjected to muscle biopsy for hematoxylin and eosin staining and enzyme histochemistry. Clinical, biochemical, and electrophysiological features in all these patients with limb-girdle muscle disease were nonspecific, and no conclusion regarding the underlying cause could be drawn from these investigations. On hematoxylin and eosin staining, 12 patients were diagnosed as muscular dystrophy, inflammatory myopathy with characteristic appearance of polymyositis was diagnosed in 4 patients, and 3 patients had normal muscle histology. After enzyme histochemistry, one patient was identified having mitochondrial myopathy. A brief case summary of the only patient diagnosed as isolated mitochondrial myopathy in our study is presented.